A Case Study About the Perception of Food Safety in Consumers of Fresh Produce from Local and Small Farmers in the North of Portugal - Ariana Macieira; Paula Teixeira (Biology and Life Sciences Forum, 2024)
Consumption of fruit and vegetables from small and local producers has increased over the years, as a result of the benefits linked to this supply chain. As consumption has increased, there has also been a rise in foodborne outbreaks associated with this type of market. Consumers are increasingly concerned about the food they eat and how it is produced. This type of market allows consumers to access such information more easily and directly, fostering a closer connection between producers and end consumers. But is food safety one of their concerns? The aim of this study was to understand what these consumers think about food safety in general and in relation to this type of market. A survey was conducted in the North of Portugal among consumers of fresh produce from local and small farmers to assess their awareness of food safety in fresh produce and their confidence in the products they consume. Only 25% of respondents admitted to having little knowledge about food safety, 46.9% stated they had a good level of knowledge, and 25% replied that they knew a lot about it. An amount of 50% said they had obtained this information through self-education and 36.4% through professional practice. Moreover, 76.7% did not believe that the products posed a risk to their health, and 16.7% said they did not know whether the products are hazardous or not. The majority of consumers perceived that they have a general knowledge of food safety and believe that the fruit and vegetables they consume from small and local producers do not pose a risk to their health. Given that 50% of consumers have obtained information about food safety on an individual basis, is this information sufficient to help them make informed purchasing decisions? The question remains.